Non-Structured Amino-Acid Impact on GH11 Differs from GH10 Xylanase - Liu, Liangwei (Public Library of Science, 2012)
The Aspergillus niger xylanase (Xyn) was used as a model to investigate impacts of un-structured residues on GH11 family enzyme, because the β-jelly roll structure has five residues (Ser1Ala2Gly3Ile4Asn5) at N-terminus and two residues (Ser183Ser184) at C-terminus that do not form to helix or strand. The N- or/and C-terminal residues were respectively deleted to construct three mutants. The optimal temperatures of XynΔN, XynΔC, and XynΔNC were 46, 50, and 46°C, and the thermostabilities were 15.7, 73.9, 15.5 min at 50°C, respectively, compared to 48°C and 33.9 min for the Xyn. After kinetic analysis, the substrate-binding affinities for birch-wood xylan decreased in the order XynΔC>Xyn>XynΔNC>XynΔN, while the K(cat) values increased in the order XynΔC<XynΔNC<Xyn<XynΔN. The C-terminal deletion increased the GH11 xylanase thermostability and T(opt), while the N- and NC-terminal deletions decreased its thermostability and optimal temperature. The C-terminal residues created more impact on enzyme thermal property, while the N-terminal residues created more impact on its catalytic efficiency and substrate-binding affinity. The impact of non-structured residues on GH11 xylanase was different from that of similar residues on GH10 xylanase, and the difference is attributed to structural difference between GH11 jelly-roll and GH10 (β/α)(8).